Historical droughts in Southeast Australia recorded in a New South Wales stalagmite. (April 2021) - Scroxton, Nick; Walczak, Maureen; Markowska, Monika; Zhao, Jian-xin; Fallon, Stewart
The Murray Darling Basin contains 40% of Australia's farms and is subject to multi-year droughts that put severe pressure on southeast Australia's freshwater resources. Yet the long-term frequency, timing and potential severity of these droughts is unknown, as there are few high-resolution paleoclimate records from the basin that extend past the instrumental era. In this study, we investigate the potential of stalagmites from Careys Cave, Wee Jasper, in the Murray-Darling Basin to record past droughts. We use a multiproxy approach of stalagmite stable isotopes, trace element data, and climate reanalysis. We show that (a) stalagmite δ 18 O at this site likely records either local or regional precipitation amount and (b) stalagmite δ 18 O shows reasonable coherence with decadal-scale wet and dry changes in regional rainfall over the last 150 years, including the Federation Drought (1895–1902). Therefore, stalagmites from Wee Jasper can be used to draw regional inferences about past rainfall and have potential to extend the record of past droughts in the Murray Darling Basin beyond the limits of historical data. Extracting such a record will enable a better understanding of the causes of multi-year droughts in the region and consequently better planning, mitigation, and resilience in the basin.